Epidemiologia e genética populacional do lobo guará, Chrysocyon brachyurus (Illiger, 1915) (Carnívora, Canidae) no nordeste do estado de São Paulo - Mattos, Paulo Sergio Ribeiro de (2003)
This study was accomplished in the northeastern area of the state of São Paulo, obtaining biological material of maned wolves for the epidemiology (parasitic diseases) and populacional genetic study. The occurrences of deaths were also verified and the relationships between the farmers and wolves were appraised. In the studies of parasitic diseases, infestations by ancilostomídeos, tricurídeos, estrongilídeos, ascarídeos, Dypilidium sp., coccídeos, Dioctophyme renale, ticks and fleas were detected. The inedited parasitosis occurrences by Hymenolepis sp and Prosthenorchis sp were verified. in the parasitoses, it was possible to detect hematological alterations of animals infected by ancilostomídeos, Hymenolepis sp., coccídeos and ticks. The populational genetic studies were accomplished with proteic markers, to evaluate the heterozygosity and the existence of populational structuring in the area. The polymorphysm degree (20%) verified in this study does not differ from the values that were verified by other authors in maned wolves and others wild canids populational studies. F statistics indicated that there were not significant reduction of the heterozygosity in the sample. This test also indicated that there was not a populacional structuring in the area, indicating that the Moji Guaçu and Pardo rivers were not characterized as a gene flow block to the species. In this area, three translocations to the interior of the Ecological Station of Jataí were verified. Also verified four death by road kill accident in the highways, one death by firegun and an occurrence of an sub-adult animal with strong dehydration and caquexis. The main problems associated with the conservation of the species, identified by the inhabitants relates of the area were the domestic avian predation, the access to the garbage and supertitions. The preservative actions discussed in the present work include the establishment of the parasitic monitoring program in wolves, promotion of critic attitudes in relation to the translocations, traffic signs in highways and implementation of environmental education programs involving adults and childrens resident in the area.